Religion and Time. - Balslev; Mohanty (Editors) (Numen Book Series, 1992)
The essays in this volume, all freshly written for this purpose, focus on the concept of time in the major religious traditions. Two essays prepare the methodological grounds - by elaborating the phenomenological and existential conceptions of time and their religious significance. The theme of time, so central to the religious point of view, offers a focal point for fruitful interreligious dialogue. The essays also demonstrate that the complexities of the understanding of time in any religious tradition no longer permit the use of familiar but outdated clichés.